INVENTARISASI PRODUK SKINCARE YANG BEREDAR DI MEDIA SOSIAL INSTAGRAM - Sindi Bella Lestari; Rahmiati Rahmiati (Jurnal Tata Rias dan Kecantikan, 2021)
Women generally use skincare but some people don't attach importance to BPOM and halal distribution permits in skincare products. Because of the many skincare products circulating on Instagram. So it is necessary to do a Product Inventory, so that people can find out information about various skincare products circulating on social media Instagram. This research has a goal, namely: 1) Knowing what types of skincare products are circulating on Instagram social media. 2) Knowing the percentage of skincare products circulating on Instagram social media that have been BPOM. 3) Knowing the percentage of skincare products circulating on Instagram social media that have a halal label. The type of research carried out is quantitative descriptive research. This research was conducted on Instagram Social Media. Research time in July 2021 until agust 2021. The variable in this study is the Inventory of skincare products circulating on Instagram Social Media. The population in this study is the Instagram account of 10 local skincare brands selling exclusively. The data used in this study is based on the source of secondary data. Data collection techniques used in this study are observation and identification. The research instrument is a measuring instrument used in a study. The data analysis technique in this study used descriptive data analysis techniques. Based on the research results, it is concluded that the types of skincare products circulating on Instagram social media are various types of products with various different functions that are sold exclusively including facial wash, toner, day cream, night cream and serum. The results of the study show that the skincare brand does not issue just 1 product for each type of product, but for 1 type of product the skincare brand issues a variety of different series according to their benefits. The percentage of skincare products circulating on social media Instagram that already have a BPOM distribution permit with a percentage of 94% but there are some products that do not have a BPOM distribution permit with a percentage of 6%. The percentage of skincare products circulating on social media Instagram that already have a halal label with a percentage of 25% and 75% do not have a halal label. even 4 out of 10 skincare brands do not have a halal label. Students majoring in Makeup and Beauty are advised to be more careful in choosing skincare products to use